Social construction of suicide in the Philippines based on the perspectives of undergraduate students from two universities in Metro Manila - Quintos, Mark Anthony (Social Sciences and Development Review, 2022)
A total of 308 undergraduate students from a sectarian, predominantly middle and upper-middle socio-economic class university (n=139) and a stateowned, non-sectarian, predominantly lower socio-economic class university (n=169) were engaged in a survey research that attempted to understand their perceptions on suicide as a phenomenon. Results indicate that the students from the two universities are very similar in their social constructions of the reality of suicide among the Filipino youth: they believe that suicide is primarily due to depression and other mental illnesses, that majority of young Filipinos have thought of suicide at least once, and that almost 1 out of every 3 has attempted the act. While they generally maintain that all members of the youth are at-risk of suicide, many also believe that the risk is particularly high for youth exposed to violence and members of the LGBT. They also tend to believe that suicide is a cry for help and that they are willing, capable, and even duty-bound to help in cases of suicide. The students believe that suicide is a topic often considered taboo in the Philippines but one that needs to be a part of more conversations. Finally, the students are generally undecided on the acceptability of suicide but also disagree with the notion that suicide can never be justified. The findings suggest that the Philippines, particularly its youth, may be ready for conversations and mobilizations in favor of suicide prevention but are still unprepared for the premise of suicide and assisted suicide as justifiable actions.